Cybercrime And Transnational Criminal Law: Tackling Online Fraud and Identity Theft - Mulyana, Yusep (PT. Anagata Sembagi Education, 2025)
The development of information and communication technology has presented new opportunities as well as challenges in the life of the global community. One of the negative impacts of digital transformation is the emergence of various forms of cybercrime, especially online fraud and identity theft. These two crimes have transnational characteristics so that they are difficult to deal with with national law alone. This study uses a normative juridical method with a qualitative approach to analyze national regulations and relevant international legal instruments in countering cybercrime. The results of the study show that Indonesia already has a legal basis through the ITE Law, the Criminal Code, and the Personal Data Protection Law, but still faces obstacles in terms of jurisdiction, capacity of law enforcement officials, and limitations of international agreements. At the global level, the Budapest Convention on Cybercrime and the United Nations Convention against Transnational Organized Crime (UNTOC) are important instruments, although their implementation is limited by the lack of universal state participation. Therefore, it is necessary to strengthen national regulations, increase international cooperation through extradition mechanisms and mutual legal assistance, and digital literacy of the public to prevent the widespread impact of online fraud and identity theft.